Historic paths and future expectations: The macroeconomic impacts of the offshore wind technologies in the UK. (September 2017) - Graziano, Marcello; Lecca, Patrizio; Musso, Marta
Abstract: Offshore wind power (OSW) plays a key role within the UK strategy for a transition towards a low-carbon economy, offering vast potential for establishing a high-tech manufacturing industry. Previous experiences in the onshore sector (OWP) suggest the UK might fail in fully capturing these macroeconomic benefits. In this work, we investigate the history of UK renewable policies, comparing its national strategy to those of other major OSW-export countries. Through the use of a numerical general equilibrium model, we quantify the macroeconomic impacts under three scenarios: a baseline, which relies on previous estimates and foresee limited local content; a 'contamination' scenario, where the UK content reaches the same levels of OWP; and a 'non-myopic' scenario, where investors expect governmental support to decrease or disappear, replicating a common path of past renewable policies. We identify the UK as a FDI-oriented country. Our results suggest that increasing the share of locally-sourced capital goods in OSP to OWP-level could generate larger income and employment effects in the UK economy. We find that under forward-looking investors the economic benefits are significantly lower than the case of myopic agents. Our results show an inherent conflict with stated purposes of UK policy for OSW. Highlights: Offshore wind can fulfil both manufacturing and environmental objectives in the UK. Historic energy policy paths in the UK and other EU countries are compared. UK lag in establishing a national industry consistent with policy framework. CGE model identifies benefits for cross-sectorial local content. Lack of stability in past policies can reduce overall benefits.